Vitamin and mineral supplements and exercise - Lukaski, H. C. (1998)
As athletes seek to gain a competitive edge in performance, they search for technical, psychological and biological advantages. One factor that is actively investigated is the use of nutritional supplements. Information is reviewed that indicates that nutritional supplementation only benefits athletes with a medically proven deficiency of a specific nutrient. General use of some vitamin and mineral supplements without evidence of nutritional deficiency may result in the development of adverse consequences for health and performance. Individuals concerned about their nutritional status should seek consultation from a dietitian to assess the quality of the diet consumed or a physician for additional evaluation. For the public in general, use of vitamin and mineral supplements is not recommended. Reliance on a diet containing a variety of foods is preferred to consumption of nutritional supplements. However, if an individual chooses to consume a nutritional supplement, one should select a commercial preparation that contains vitamins and minerals in amounts equal to the recommended daily allowance or estimated safe daily dietary allowance. This information will be useful to physically active people who are concerned about their performance, health and well being.